STUDENTS ATTITUDES REGARDING THE ETHICS OF EARNINGS MANAGEMENT ACTIVITIES: AN EMPIRICAL INVESTIGATION - CUZDRIOREAN, Dan Dacian (Annales Universitatis Apulensis Series Oeconomica, 2013)
The objective of this paper is to assess the ethics of short-term earnings management in a code-law country. In order to understand the morals of short-term earnings management we conducted a survey using students as respondents. Even if we found disagreement among our respondents, the findings of this study document that ethical acceptance of short-term earnings management depends on the type of manipulation (e.g. accrual-based earnings management versus real earnings management). Also, the results indicate that students with higher moral development evaluate short-term earnings management practices as less ethical and are less likely to accept it. The paper concludes with a discussion of the implications and suggestions for future research.